Vitamin B1 Helps to Limit Mycobacterium tuberculosis Growth via Regulating Innate Immunity in a Peroxisome Proliferator-Activated Receptor-γ-Dependent Manner - Hu, Shengfeng; He, Wenting; Du, Xialin; Huang, Yulan; Fu, Yuling; Yang, Yalong; Hu, Chuxuan; Li, Silin; Wang, Qinshu; Wen, Qian; Zhou, Xinying; Zhou, Chaoying; et al. (Frontiers in Immunology, 2018)
It is known that vitamin B1 (VB1) has a protective effect against oxidative retinal damage induced by anti-tuberculosis drugs. However, it remains unclear whether VB1 regulates immune responses during Mycobacterium tuberculosis (MTB) infection. We report here that VB1 promotes the protective immune response to limit the survival of MTB within macrophages and in vivo through regulation of peroxisome proliferator-activated receptor γ (PPAR-γ). VB1 promotes macrophage polarization into classically activated phenotypes with strong microbicidal activity and enhanced tumor necrosis factor-α and interleukin-6 expression at least in part by promoting nuclear factor-κB signaling. In addition, VB1 increases mitochondrial respiration and lipid metabolism and PPAR-γ integrates the metabolic and inflammatory signals regulated by VB1. Using both PPAR-γ agonists and deficient mice, we demonstrate that VB1 enhances anti-MTB activities in macrophages and in vivo by down-regulating PPAR-γ activity. Our data demonstrate important functions of VB1 in regulating innate immune responses against MTB and reveal novel mechanisms by which VB1 exerts its function in macrophages.